Climate Scenarios: What we need to know and how to generate them - Santoso, H.; Idinoba, M.; Imbach, Pablo (Center for International Forestry Research, 2008)
Climate change profoundly affects the natural and social environment. Decision-makers and resource managers require information regarding future changes in climate average and variability to better anticipate potential impacts of climate change. This book provides some overviews on the roles of climate scenarios in adaptation planning and what should be considered in using and generating climate scenarios, in a frequently ask questions style. Specifically, this book tries to answer questions commonly addressed by non-climatologists when they want to address climate scenario in adaptation plans. It covers topics on the need of climate scenarios for adaptation, types of climate data or information we need, different types of climate scenarios, emission scenarios, choosing general circulation model (GCM), how to modify the spatial and temporal resolution of climate data, how to deal with uncertainties, and the progress of the climate models in assessing extreme events. The book also provides additional information regarding tools and sources of data in relation to climate scenario.